Peran Guru Pendidikan Agama Islam dalam Menanamkan Nilai-Nilai Karakter Peserta Didik di SMP Al-Ijtihad - Muin, M. Tamsil; Abnisa, Almaydza Pratama (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the role of Islamic Religious Education teachers in instilling character values of students at Al-Ijtihad Junior High School. This study uses a type of field research. The data collection technique uses field observation, interview, and documentation methods. Data analysis was carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the analysis show that the role of Islamic Religious Education teachers in instilling the character values of students is always active in Al-Ijtihad Junior High School. The pie teacher always guides students to always have good speech, good manners to parents and teachers, students make a habit outside the classroom, namely when meeting the teacher to say greetings, speak well and politely, respect and kiss the teacher's hand. Furthermore, teachers also always invite students to instill the value of religious character in school, namely tadarus Al-Qur'an, dhuha prayer, hajat prayer and dzuhur prayer in congregation